Pro underground water system / Nor Hamiza Mohd Noor … [et al.] - Mohd Noor, Nor Hamiza; Sabri, Muhammad Farid; Abdul Malek, Faiz Danail; Razali, Nur Fitrah; Wan Johan, Wan Muhammad Harith Shah; Nordin, Mohamad Nazmi (Division of Research and Industry Linkages, 2017)
PuRoses is the new essence of air purifier in this century. This essence is made from the French rose bud, freshly picked from the mountains of Turkey. It helps to reduce the smoking addiction especially for heavy smokers. Moreover, it can help to overcome sleepiness among the students and employees. Furthermore, the smell of PuRoses helps to enhance one's mood into calmness and boosting positive aura. It can be effectively and safely used by everyone especially students who are trying to be more focused in the study environment.